strent433
strent433
12-05-2017
Mathematics
contestada
solve for y when x=-2
-9x-3y=6
Respuesta :
cher
cher
14-05-2017
-9x - 3y = 6, x = -2
Plug in -2 for x.
-9(-2) - 3y = 6
Simplify.
18 - 3y = 6
Subtract 18 from both sides.
-3y = 6 - 18
Simplify.
-3y = -12
Divide both sides by -3.
y = -12/-3
Simplify.
y = 4
~Hope I helped!~
Answer Link
VER TODAS LAS RESPUESTAS ( 51+ )
Otras preguntas
Daniel and Saquon are each saving money. Daniel starts with $50 in his savings account and adds $8 per week. Saquon starts with $65 in his savings account and a
I keep lighting candles
HELPP I PUT MORE POINTS
What are properties of a base
the radio waves from your cell phone go through the air and are received by a ??
A restaurant owner washed 94 kilograms of vegetables, some spinach and some cucumbers. The spinach came in 10-kilogram bags and the cucumbers came in 9-kilogram
Help Me 15 POINTS What does a touch ring allow an artist to do on a digital tablet? A. draw shapes using it like a pen B. right-click and double-click like a
please help i’ll mark brainliest
Jacob can drive 42 miles per gallon in his new hybrid car. He needs to drive 336 miles next week. How many gallons of gas will Jacob need to drive next week?
WILL GIVE BRAINLIEST FOR HELP (5x3−2x2+3x−8)-(3x2−4x−1) and then the result of that minus 4x − x2 + 5